Impact of crop bio- intensification and nutrient management on growth, yield and yield attributes of rice crop under North West Himalayan region of Jammu-Kashmir: Crop bio- intensification and nutrient management of rice - Singh, Permendra; Singh, Shashank Shekher; Singh, S.K. (ORYZA-An International Journal of Rice, 2024)
The experiment was performed in rabi, zaid and kharif seasons of 2018-19 and 2019-20 to study the bio-intensification possibilities in different cropping systems at Research Farm, Main Campus, Chatha, SKUAST-Jammu, Jammu & Kashmir, India .The experiment was laid out in randomized block design (factorial)/ DMRT with 15 treatments and three replications. Among the crop bio-intensification, rice crop sown under wheat (FIRB)+lentil (B)-summer moongbean -BM+rice (F)+moongbean (B) practice produced significantly higher panicle per meter row length, tillers per meter row length than the crop sown under wheat - rice during both the years of experimentations. Whereas, rice crop sown under wheat-rice practice produced significantly higher grain yield (35.42 q/ha and 36.65 q/ha), than the other existing crop bio-intensification practice during both the years of experimentation. Among the nutrient management, application of 100% in- organic showed significantly higher panicle per meter row length, tillers per meter row length and yield than 100% organic (FYM) and statistically at par with INM (50:50) during both the years of experimentations.